È possibile misurare i diritti delle minoranze di religione e convinzione? (Stato, Chiese e pluralismo confessionale, 2023)
Is it possible to measure religious or belief minority rights?ABSTRACT: Is it possible to measure how much the legal systems of the European Union countries respect and promote the rights of religious or belief minorities? Based on the findings of the Atlas of religious or belief minority rights research project (https://atlasminorityrights.eu), this article answers the question in the affirmative. The paper is divided into three parts. The first briefly describes the methodology and techniques used to measure minority rights. They are determined by the answers given to some preliminary questions that are discussed in the second part of the contribution. The last section of the article outlines the purpose and value of measuring religious or belief minority rights.SOMMARIO: 1. Introduzione - 2. La misurazione dei diritti delle minoranze di religione e convinzione - 3. L’oggetto e i confini della misurazione - 4. L’utilità della misurazione.